Next stop, implementation: collaborative monitoring to inform adaptive policy-making and implementation - L. M. Hermans; M. Haasnoot; J. H. Kwakkel (Proceedings of the International Association of Hydrological Sciences, 2014)
Dynamic Adaptive Policy Pathways has been developed as an approach to deal with deep uncertainties and support robust decision-making for long-term planning. Given the unpredictable and uncertain futures, implementation of the resulting adaptive policies needs to be informed by regular monitoring. However, monitoring implementation in practice is complicated by the need to coordinate activities and share information among multiple actors. Here we present a first outline for an approach to organise collaborative monitoring to support adaptive implementation of long-term water policies. The analytical basis rests on an extension of Dynamic Adaptive Policy Pathways with actor analysis principles. Monitoring is to be organised around adaptation tipping points, for which a set of questions needs to be addressed that put societal actors central. Examples from two water management cases in the Netherlands suggest the usefulness of this approach.